Antibody-Mediated LILRB2-Receptor Antagonism Induces Human Myeloid-Derived Suppressor Cells to Kill Mycobacterium tuberculosis - Singh, Vipul K.; Khan, Arshad; Xu, Yitian; Mai, Sunny; Zhang, Licheng; Mishra, Abhishek; Restrepo, Blanca I.; Pan, Ping-Ying; Chen, Shu-Hsia; Jagannath, Chinnaswamy (Frontiers in Immunology, 2022)
Tuberculosis is a leading cause of death in mankind due to infectious agents, and Mycobacterium tuberculosis (Mtb) infects and survives in macrophages (MФs). Although MФs are a major niche, myeloid derived suppressor cells (MDSCs) are an alternative site for pathogen persistence. Both MФs and MDSCs express varying levels of Leucocyte Immunoglobulin-like Receptor B (LILRB). The LILRB family members regulate the myeloid cell suppression function. Herein, we demonstrate that antagonism of LILRB2 by a monoclonal antibody (mab) increased a switch of human MDSCs towards M1-macrophage phenotype increasing the killing of intracellular Mtb. Mab mediated antagonism of LILRB2 alone and its combination with pharmacological blockade of SHP1/2 kinase increased proinflammatory cytokine responses and phosphorylation of ERK1/2, p38 MAPK and NF-kB in Mtb infected MDSCs. LILRB2 antagonism also upregulated anti-mycobacterial iNOS gene expression and was associated with an increase in both nitric oxide and reactive oxygen species synthesis. Because genes associated with the anti-microbial function of M1-MФs were enhanced in MDSCs following mab treatment, we propose that LILRB2 antagonism reprograms MDSCs from an immunosuppressive state towards inflammatory phenotype enhancing the killing of Mtb. LILRB2 is therefore a novel therapeutic target for eradicating Mtb in MDSCs.